2008
DOI: 10.2527/jas.2007-0478
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of cow and beef muscles: Benchmarking the differences and similarities1,2

Abstract: The objective of this study was to identify muscles from cow populations that are equivalent or may possibly be made equivalent to muscles from A-maturity, Select-grade cattle in terms of chemical, compositional, and color characteristics. Objective color, expressible moisture, proximate composition, pH, heme iron concentration, and total collagen content were determined for 9 muscles (M. gluteus medius, M. infraspinatus, M. longissimus dorsi, M. psoas major, M. rectus femoris, M. tensor fascia latae, M. teres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
32
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 33 publications
8
32
1
5
Order By: Relevance
“…Apart from the USA (Rhee et al, 2004;Von Seggern et al, 2005), studies regarding muscle profiling have been conducted in different countries including Norway (Hildrum et al, 2009) and Poland (Zajac et al, 2011). Ranking of muscles may differ according to animal gender and age (Hildrum et al, 2009;Patten et al, 2008).Thanks to the development of genomics, more modern techniques such as transcriptomics (Cassar-Malek et al, 2009) and proteomics (Guillemin et al, 2011) are available nowadays to better characterise individual muscles according to tenderness score or to livestock systems. These methods could be considered as modern ones for muscle profiling.…”
Section: Muscle Profilingmentioning
confidence: 99%
“…Apart from the USA (Rhee et al, 2004;Von Seggern et al, 2005), studies regarding muscle profiling have been conducted in different countries including Norway (Hildrum et al, 2009) and Poland (Zajac et al, 2011). Ranking of muscles may differ according to animal gender and age (Hildrum et al, 2009;Patten et al, 2008).Thanks to the development of genomics, more modern techniques such as transcriptomics (Cassar-Malek et al, 2009) and proteomics (Guillemin et al, 2011) are available nowadays to better characterise individual muscles according to tenderness score or to livestock systems. These methods could be considered as modern ones for muscle profiling.…”
Section: Muscle Profilingmentioning
confidence: 99%
“…Estudos relacionam aspectos como a idade sobre a expressão da coloração e textura da carne (7,17) . Além disso, a intensidade de exercício físico (17) e o nível de glicogênio muscular pré-abate dos animais (18) também são variáveis que refletem na coloração. Não houve correlação entre a idade e coloração (P=0,2384; r= -0,1987), já entre a idade e textura a correlação foi negativa (r= -0,53; P= 0,0008).…”
Section: Resultsunclassified
“…Poderiam-se esperar melhorias na maciez da carne das vacas com maior grau de acabamento, uma vez que essas, possivelmente, foram submetidas a dietas de maior aporte energético, conforme discutido anteriormente, o que, associado à semelhança no tempo de terminação e idade de abate, promoveria tendência de melhorias na maciez. Em virtude disso, aspectos relacionados à modulação de fibras musculares (18) e maior solubilidade do colágeno (19) em vacas que recebem maior aporte energético favorecem melhorias na maciez da carne, principalmente quando a idade de abate das vacas é similar, conforme verificado no presente estudo (60 contra 68 meses, respectivamente, para os graus de acabamento >6 e <6).…”
Section: Resultsunclassified
“…Weber et al (2013) observed that an increase in energy intake in the diet of cows promoted improvements in the tenderness of the meat, which was attributed by the authors to increased solubility of collagen. Other studies have shown that variations in the energy density of the diet could modify the tenderness as a function of the modulation of muscle fibers (Patten et al 2008, Sawyer et al 2004. Possibly the trend observed in this study may be associated with differences in the time of termination of cows in feedlot or pasture, so that those subject to termination for a period of longer (pasture) had higher solubility of collagen and therefore improvements in meat tenderness.…”
Section: Resultsmentioning
confidence: 99%
“…The same tenderness was observed for the palatability which, correlated with the tenderness, the panel (r = 0.61, P = 0.0004) and Shear (r = -0.70, p <0.0001); showing no significant differences. Oury et al (2009) In a current rewiew, the effect of food on the characteristics of the meat (Patten et al 2008, Vastergaard et al 2000, 2007, Weber et al 2013) hadn´t significant influence of the termination systems of cattle (Table V). Even with differences in the time of termination of cows, 79 and 92 days; respectively for the feedlot and pasture, it was not enough to promote changes in most qualitative aspects of meat covered in this study.…”
Section: Resultsmentioning
confidence: 99%